Quantitative assessment of Pakistan and China free trade agreement - Ch. Mazhar Hussain; Syed Zulfiqar Ali Shah (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2017)
The purpose of this paper is to assess the economic impact of tariff eliminations under free trade agreement (FTA) of Pakistan and China on various macroeconomic and trade variables. The objective is to scrutinize the pre and post effect of Pakistan and China FTA on macroeconomic factors like real gross domestic product (GDP), trade balance, output and trade in different sectors, welfare in context of Pakistan. In this regard, the computable general equilibrium (CGE) modeling structure of the global trade analysis project (GTAP) model and database is use to analyze the aggregate effect as well as sectorial implications. The GTAP database version 9 has data of 140 countries. Nevertheless, 2 main countries such as Pakistan and China are aggregated separately. Moreover, the database also embedded with data of 57 sectors, which have been aggregated into 43 sectors. The simulation results reveal that under tariff eliminations of Pakistan and China FTA, Pakistan faces negative impact on its economy whereas China gets benefit from the same. China gains in terms of welfare, real GDP and trade balances, while Pakistan losses in terms of welfare, real GDP and trade balances. However, the results identify the potential exports sectors of Pakistan such as textile, wearing apparel, leather products, plant-based fibers, chemical products, vegetable oil and fats, and metal products. Therefore, Pakistan can exploit this opportunity by increasing exports from these sectors to China. This study is useful for policy makers to design appropriate trade policy of Pakistan.
Keywords: 330; Free trade agreement (FTA); Pakistan; China; global trade analysis project (GTAP); computable general equilibrium (CGE)